Plant materials for soil fertility management in subhumid tropical areas - Kayuki, KC; Wortmann, Charles S. (Wiley, 2001)
Lantana camara L., Senna hirsuta (L.) Irwin & Barneby, Tithonia diversifolia (Hemsl.) A. Gray, and Aspilia kotschyi du Petit-Thouars occur naturally in eastern and central Uganda. Trimmings of these species were evaluated for effectiveness in improving soil productivity. The plant trimmings varied for N (13 30 g kg?1), P (1.1 1.8 g kg?1), lignin (11 16%), and polyphenol (1.3 2.5%) concentration. Decomposition rates were higher for incorporation than for surface placement, but placement did not affect maize (Zea mays L.) and bean (Phaseolus vulgaris L.) yield. Decomposition rates were similar for all species with the same placement method. Potassium and Mg were generally mineralized most and least rapidly, respectively, with intermediate rates for N, P, and Ca. Maize and bean yield increased with application of 4 Mg ha?1 dry wt. trimmings of L. camara, S. hirsuta, and T. diversifolia, but only maize eventually responded to A. kotschyi Yields per units of N and P applied were more and less, respectively, with inorganic than with organic treatments, but plant trimmings supplied less P than fertilizer. At the end of the trial period, available soil P was more for the full rate of fertilizer than for the mean of the plant materials. Combining L. camara and fertilizer, at 50% rates, resulted in an average of 0.22 Mg ha?1 more yield than expected from mere additive effects of the organic and inorganic resources. The value of plant materials may be enhanced by balancing nutrient supply with inorganic fertilizers.